2019
DOI: 10.1177/0300060519875336
|View full text |Cite
|
Sign up to set email alerts
|

Application of a three-dimensional printed segmental scapula prosthesis in the treatment of scapula tumors

Abstract: Chondrosarcoma is characterized by the presence of histologically aggressive behavior, and commonly involves the scapula. Currently, limb salvage surgery is the recommended surgical treatment. Owing to the irregularity of the tumor, the suitability of an implant after tumor resection is a challenge for surgeons. Three-dimensional (3D) printing technology has the potential to make personalized limb salvage surgery a reality. We report the case of a 53-year-old man who was diagnosed with chondrosarcoma of the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…A 3D-printed, patient-specific implant replacement following giant cell tumor of the distal radius and proximal phalanx was feasible and resulted in satisfying functional outcomes [ 41 , 42 ]. Similar results were reported for patients with osteosarcoma in the humerus [ 43 ], leiomyosarcoma of the radius [ 43 ], and chondrosarcoma of the scapula [ 44 , 45 ] or the humerus [ 46 ]. Patients with advanced Kienböck disease treated with an os lunatum excision followed by a titanium lunate replacement showed significantly improved wrist function and reported remarkable pain relief [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 81%
“…A 3D-printed, patient-specific implant replacement following giant cell tumor of the distal radius and proximal phalanx was feasible and resulted in satisfying functional outcomes [ 41 , 42 ]. Similar results were reported for patients with osteosarcoma in the humerus [ 43 ], leiomyosarcoma of the radius [ 43 ], and chondrosarcoma of the scapula [ 44 , 45 ] or the humerus [ 46 ]. Patients with advanced Kienböck disease treated with an os lunatum excision followed by a titanium lunate replacement showed significantly improved wrist function and reported remarkable pain relief [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 81%
“…The patient was satisfied with the results of the surgery and showed a good functional score (Constant score: 68 points). Deng et al [ 11 ] reported a patient with grade 1 chondrosarcoma treated with a 3-D printed segmental scapula prosthesis. Although the tumor was located at Malawer S1, it involved both the supraspinatus and infraspinatus lesions, which means that all rotator cuff muscles were resected during the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Faced with the need to obtain increasingly complex reconstructive results, the introduction of custom reconstruction techniques using 3D printing has led to significant changes in surgical outcomes in oncological and reconstructive orthopedics. Furthermore, using customized cutting masks on the patient's bone profile has increased the possibility of obtaining large surgical margins with increasingly complex osteotomies and subsequently allowing prosthetic reconstructions that adhere perfectly to the healthy portion of bone [23,24]. In our case, the presence of central low-grade osteosarcoma involving the scapula at the level of the glenoid cavity with the involvement of part of the body and with a partial extension at the level of the acromial and coracoid process (Malawer S1 and S2), set the limit of a total scapulectomy.…”
Section: Discussionmentioning
confidence: 99%